Companion mathematica notebook for 'The physical basis of mollusk shells chiral coiling -- a twisted history' - Moulton, D (University of Oxford, 2021)
This is a companion Mathematica notebook for reproducing the results contained in the publication, 'The physical basis of mollusk shells chiral coiling -- a twisted history', in the journal PNAS.